Research on the Impact of Hydro-PV Complementary System Operation on Power Grid Based on New Energy Consumption. (22nd April 2022) - Zhao, Xunxin; Ren, Yan; Sha, Yongbing; Zhang, Linlin; Hou, Shangchen; Xiao, Fengming; Chen, Feiming; Chen, Shudong; He, Kuidong; Luo, Lijun; Jiang, Xiaofeng
Abstract : Considering the random, intermittent, and periodic characteristics of photovoltaic (PV) power generation, its active output must be compensated and regulated by other conventional power sources. Taking the Longyangxia hydropower station as an example, this study models the output of PV generator sets and hydropower units under different conditions, taking into account the influence of weather and seasonal factors on the characteristics of PV power generation and hydropower generation. We also analyze the hydro-PV resource distribution and output characteristics of Longyangxia and construct the integration of hydro-PV complementary in Longyangxia. The impact of hydro-PV integration on the power grid is discussed in terms of other new energy consumption and peaking capacity, and the impact of the Yellow River water dispatch and downstream gradient power generation. It is demonstrated that hydropower is a good complementary resource to PV power generation, which not only improves the quality of the grid but also enhances the new energy consumption capacity. Through the construction of the Longyangxia hydro-PV complementary project, it can increase the economic benefits of the power grid and play an important role as a reference for subsequent projects.